Central Banking and Financial Stability in the Long Run - Jin Cao; Lorán Chollete (Center for Economic Studies and ifo Institute (CESifo), 2013)
Most theoretical central bank models use short horizons and focus on a single tradeoff. However, in reality central banks play complex, long horizon games and face more than one tradeoff. We account for these issues in a simple infinite horizon game with a novel tradeoff: higher rates deter financial imbalances, but lower rates reduce the likelihood of bankruptcy. We term these factors discipline and stability effects, respectively. The central bank's welfare decreases with dependence between real and financial shocks, so it may reduce costs with correlation-indexed securities. Generally, independent central banks cannot attain both low inflation and financial stability.
Keywords: E50; G21; G28; 330; central bank; correlation-indexed security; discipline effect; stability effect